Uplift of the central transantarctic mountains. Issue 1 (December 2017) - Wannamaker, Phil; Hill, Graham; Stodt, John; Maris, Virginie; Ogawa, Yasuo; Selway, Kate; Boren, Goran; Bertrand, Edward; Uhlmann, Daniel; Ayling, Bridget; Green, A. Marie; Feucht, Daniel
Abstract The Transantarctic Mountains (TAM) are the world's longest rift shoulder but the source of their high elevation is enigmatic. To discriminate the importance of mechanical vs. thermal sources of support, a 550 km-long transect of magnetotelluric geophysical soundings spanning the central TAM was acquired. These data reveal a lithosphere of high electrical resistivity to at least 150 km depth, implying a cold stable state well into the upper mantle. Here we find that the central TAM most likely are elevated by a non-thermal, flexural cantilever mechanism which is perhaps the most clearly expressed example anywhere. West Antarctica in this region exhibits a low resistivity, moderately hydrated asthenosphere, and concentrated extension (rift necking) near the central TAM range front but with negligible thermal encroachment into the TAM. Broader scale heat flow of east-central West Antarctica appears moderate, on the order of 60–70 mW m−2, lower than that of the U.S. Great Basin. The source of the Transantarctic Mountains' high elevation has remained unclear. Here, the authors present data from a 550 km long magnetotelluric geophysical transect showing that uplift is likely to be mechanical via cantilevered flexure along a master boundary fault and not upper mantle or lower crustal thermal mechanisms.